Reduction of Lattice Thermal Conductivity in PbTe Induced by Artificially Generated Pores - Jae-Yeol Hwang; Eun Sung Kim; Syed Waqar Hasan; Soon-Mok Choi; Kyu Hyoung Lee; Sung Wng Kim (Advances in Condensed Matter Physics)
Highly dense pore structure was generated by simple sequential routes using NaCl and PVA as porogens in conventional PbTe thermoelectric materials, and the effect of pores on thermal transport properties was investigated. Compared with the pristine PbTe, the lattice thermal conductivity values of pore-generated PbTe polycrystalline bulks were significantly reduced due to the enhanced phonon scattering by mismatched phonon modes in the presence of pores (200 nm–2 μm) in the PbTe matrix. We obtained extremely low lattice thermal conductivity (~0.56 W m−1 K−1 at 773 K) in pore-embedded PbTe bulk after sonication for the elimination of NaCl residue.